2009
DOI: 10.2298/bah0902101a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic biodiversity studies on IGFBP-3 gene in Egyptian sheep breeds

Abstract: The insulin-like growth factor binding protein-3 (IGFBP-3) gene is a structural gene associated with the growth and development of the animals. The present investigation was carried out to study DNA polymorphism by PCR-RFLP of IGFBP-3 gene in four Egyptian local sheep breeds and its comparison with Indian sheep breeds. Genomic DNA was isolated from a total of 20 animals from four Egyptian breeds of sheep namely Rahmani, Ossimi, Awassi, and Barki. A fragment of IGFBP-3 gene, comprising of a part of exon 2, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…This agrees with the previous study (Saleh et al, 2019) that the digestion of IGFBP-3 with HaeIII yielded one RFLP pattern for goats, and for buffalo, one genotype (AA) was found when HaeIII and TaqI restriction enzymes were used separately, while three genotypes were found for cattle. Also, the current results agree with those of Ali et al, (2009) who reported that the RFLP pattern for IGFBP-3/HaeIII obtained for some sheep breeds yielded one pattern of five fragments sized 201, 201, 87, 67, and 57 bp. Also, with Kumar et al, (2006) who studied the genetic diversity among Indian sheep breeds, Mandya, Marwari, Madras, Banur, and Red Muzaffarnagari for the sequence of IGFBP-3 gene digested by HaeIII and reported that the digestion profile revealed only one pattern with 8 DNA fragments for all sheep breeds and no polymorphism was detected.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with the previous study (Saleh et al, 2019) that the digestion of IGFBP-3 with HaeIII yielded one RFLP pattern for goats, and for buffalo, one genotype (AA) was found when HaeIII and TaqI restriction enzymes were used separately, while three genotypes were found for cattle. Also, the current results agree with those of Ali et al, (2009) who reported that the RFLP pattern for IGFBP-3/HaeIII obtained for some sheep breeds yielded one pattern of five fragments sized 201, 201, 87, 67, and 57 bp. Also, with Kumar et al, (2006) who studied the genetic diversity among Indian sheep breeds, Mandya, Marwari, Madras, Banur, and Red Muzaffarnagari for the sequence of IGFBP-3 gene digested by HaeIII and reported that the digestion profile revealed only one pattern with 8 DNA fragments for all sheep breeds and no polymorphism was detected.…”
supporting
confidence: 92%
“…On the other side, associations have been made between few numbers of the IGFBPs and follicle status (Besnard et al, 1996;Khalid and Haresign, 1996). Moreover, due to the important role of IGFBP-3 in animal development and growth, it is considered as a candidate gene to be utilized as a marker for production and growth traits in livestock species (Ali et al, 2009;Shafey et al, 2014;Saleh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Turning to the IGFBP3 in other ruminants, for the SNP C279A, when the HaeIII-RFLP method was used to digest DNA samples from buffaloes (Padma et al, 2004) and sheep (Ali et al, 2009;Kumar et al, 2006), only a single restriction pattern was identified, corresponding to the presence of only the CC genotype in this location. For goats, two SNPs (A78G and G217A) in intron 2 have been reported (Lan et al, 2007a(Lan et al, , 2007b.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity of sheep breeds needs to be constantly monitored because of breed substitution, indiscriminate crossbreeding and decline of population sizes of some breeds (FAO 2000). Genetic variation within a breed is important in genetic improvement programmes (Ali et al 2009). Reduction in genetic diversity of indigenous genetic resources reduces the chances that may be available in a breed to respond to changes in environment and disease patterns.…”
Section: Genetic Characterisationmentioning
confidence: 99%